ANALYSIS OF THE ALGORITHMS FOR AUTOMATIC SPATIAL ORIENTATION OF THE CLOUDS OF POINTS OBTAINED WITH A TERRESTRIAL SCANNER - Markiewicz, Jakub Stefan; Markiewicz, Lukasz Marcin (International Multidisciplinary Scientific GeoConference SGEM, 2015)
The subject of this paper is a preliminary analysis of the algorithms for automatic spatial orientation of the clouds of points obtained by using a terrestrial scanner. In the proposed data processing method, the clouds of points were treated as images projected on a spherical plane of reference, additionally enriched with a depth map. The algorithms and a library of the sets of functions used in CV were presented. The implementation of a free C++ language library with algorithms used in CV was analysed. The correctness of the tie points search and operation time was examined. Clouds of points obtained from a terrestrial laser scanner Z+F 5006H were used as the source data. The analysis presented the algorithms linking the photogrammetric approach with the approach supported by CV.